The many species of humanity - Wolpoff, Milford H.; Caspari, Rachel (Polskie Towarzystwo Antropologiczne, 2000)
Naming new human species may seem to be a harmless endeavor, of little interest to all but a few specialists playing out the consequences of different evolutionary explanations of phyletic variation, but it has significant implications in how humanity is viewed because studies of race and human evolution are inexorably linked. When essentialist approaches are used to interpret variation in the past as taxonomic rather than populational, as increasingly has been the case, it serves to underscore a typological view of modern human variation. In terms of how they are treated in analysis, there often seems to be no difference between the species, subspecies, or paleodemes of the past and the populatons or races whose interrelationships and demographic history are discussed today. This is not inconsequential because both history and current practice shows that science, especially anthropology, is not isolated from society.
Keywords: Paleoanthropology; Species of humans; Race; Trees